(untitled) (International Journal of Engineering and Computer Science, 2014)
This paper is concerned with the designing of an Application specific microcontroller that can be implemented on any FPGA. ASuC is a collection of several generic processor modules that can be integrated to facilitate any particular application in most optimized way. We are designing our project in Verilog HDL using XILINX Design Suite 14.1. The proposed architecture and simulation waveforms are presented in this paper.